Commissioning of total body irradiation using plastic bead bags. (2nd September 2020) - Akino, Yuichi; Maruoka, Shintaro; Yano, Katsuyuki; Abe, Hiroshi; Isohashi, Fumiaki; Seo, Yuji; Tamari, Keisuke; Hirata, Takero; Kawakami, Manabu; Nakae, Yoshiki; Tanaka, Yoshihiro; Ogawa, Kazuhiko
Abstract: The goal of total body irradiation (TBI) is to deliver a dose to the whole body with uniformity within ±10%. The purpose of this study was to establish the technique of TBI using plastic bead bags. A lifting TBI bed, Model ORP-TBI-MN, was used. The space between the patient's body and the acrylic walls of the bed was filled with polyacetal bead bags. Patients were irradiated by a 10 MV photon beam with a source to mid-plane distance of 400 cm. The monitor unit (MU) was calculated by dose-per-MU, tissue-phantom-ratio and a spoiler factor measured in solid water using an ionization chamber. The phantom-scatter correction factor, off-center ratio and the effective density of the beads were also measured. Diode detectors were used for in vivo dosimetry (IVD). The effective density of the beads was 0.90 ± 0.09. The point doses calculated in an I'mRT phantom with and without heterogeneity material showed good agreement, with measurements within 3%. An end-to-end test was performed using a RANDO phantom. The mean ± SD (range) of the differences between the calculated and IVD-measured mid-plane doses was 1.1 ± 4.8% (−5.9 to 5.0%). The differences between the IVD-measured doses and the doses calculated with Acuros XB of the Eclipse treatment planning system (TPS) were within 5%. For two patients treated with this method, the differences between the calculated and IVD-measured doses were within ±6% when excluding the chest region. We have established the technique of TBI using plastic bead bags. The TPS may be useful to roughly estimate patient dose.